The Nagayama’s Norio case: clues for a real juvenile justice - García Escobar, Jorge (2010)
In 1967, Japanese society was shocked when they knew the history and events leading to the arrest of a teenager named Norio Nagayama, who killed three people on a path of violence that reinforced the determination of the death penalty, valid option then and even now for the Japanese’s government as a fair resolution to cases as serious as murder. Being responsible for the murders at the time of having committed a teenager and taking into perspective the history and sentence executed today, it’s worth to question about the validity of human rights of children and adolescents in semi prison sentences or prison and the use of violence to solve teen violence This article proposes the analysis of an emblematic case of the death penalty sentence for a teenager, preparing guidelines for social and judicial practice with populations of adolescents in conflict with the law, the ultimate solution, and paragraphs of the death penalty is exposed as a contradiction of humanitarian solution, responsible, systematic based on human rights.